Healthcare reform: it is getting personal. (June 2012) - Shapiro, Steven D
Healthcare reform must deal with the challenge of reducing the cost of care while embracing the opportunity to improve care delivery. Personalized medicine will be key to developing new care models. These models will provide coordinated and continuous care delivered by a team, with the individual patient as the central member of the team. Clinical effectiveness research will identify the best care models and reduce variation for populations of patients with a given disease. Personalized medicine will apply 'big science 'omics' with a systems biology approach to define disease networks, allowing us to add back appropriate variation in care for the individual. This effort will be enhanced by the electronic health record, which, combined with deep analytics, will capture detailed phenotypic data matched with the genotype. We are at the beginning of this journey and, despite a variety of technical, economic and societal hurdles, we cannot afford to fail.